PENGARUH BIAYA CORPORATE SOCIAL RESPONSIBILITY DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN (Studi pada Perusahaan BUMN yang terdaftar di Bursa Efek Indonesia tahun 2012-2016) - Fithrishiyam Aulia Rasyid; Willy Sri Yuliandhari (Universitas Widyatama, 2018)
In general, the company has a goal to get maximum profits, prosper the shareholders or the owner of the company and make the maximum company value that can be seen in the stock price. This study aims to analyze the effect of Corporate Social Responsibility costs measured through employee welfare costs, partnership costs, community development costs and dividend policies measured by the Dividend Payout Ratio (DPR) ratio to a firm value measured through Tobin's Q ratio. The number of samples in the study These are 13 state-owned companies listed on the Indonesia Stock Exchange in 2012-2016 with data based on annual reports. The method in this study is descriptive statistics and panel data regression using software eviews version 9. The sample selection technique used is purposive sampling. Data analysis method uses panel data regression analysis with a significance of 5%. Based on the results of the study, simultaneously the Corporate Social Responsibility costs and dividend policy have an effect on the company value of 14.31%. While the remaining 85.69% is influenced by other variables outside the research. Partially, the cost of Corporate Social Responsibility does not influence the negative direction of firm value. While dividend policy has an effect on the positive direction of company value.